An ICT-based development framework - Kontakos, Ilias (Technical Centre for Agricultural and Rural Cooperation, 2013)
ICTs delivered through an appropriate development framework can help overcome the physical boundaries that limit small islands' capacity to conduct economic, political and social transactions.